Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kinerja Karyawan Pt. Metro Duta Klin - Starina Dwi Putri; Whina Ratnawati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the significant influence partially and simultaneously between compensation and work motivation on employee performance at PT. Metro Duta Klin. This research method is a quantitative method. The population used in this study were employees of PT. Metro Duta Klin. The sample used was 57 people. The analysis test in this study used a validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression analysis test, multiple linear regression analysis test, hypothesis test, simultaneous (F) test. The results of this study indicate that compensation has a significant effect on employee performance at PT. Metro Duta Klin. Based on the partial hypothesis results (t test) obtained 11.479> 2.00488 and a significant value <0.05, then the first hypothesis is accepted. Work motivation has a significant effect on employee performance Employees Based on the partial hypothesis results (t-test) 13.495 > 2.00488 and a significant value <0.05, the second hypothesis is accepted. Compensation and work motivation simultaneously have a significant effect on employee performance Because f count > f table or 97.833 > 3.16 and a significant value <0.05, the third hypothesis is accepted. The R Square value of 0.784 indicates that employee performance is influenced by Compensation and work motivation by 78.4% while the remaining 21.6% is influenced by other factors outside this study. This indicates that the influence of compensation and work motivation on employee performance at PT. Metro Duta Klin has a simultaneous effect on employee performance.